Azimuthal anisotropy of charged jet production in √sNN=2.76 TeV Pb-Pb collisions - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Physics letters, 2016)
We present measurements of the azimuthal dependence of charged jet production in central and semi-central sNN=2.76 TeV Pb-Pb collisions with respect to the second harmonic event plane, quantified as v2ch jet. Jet finding is performed employing the anti-kT algorithm with a resolution parameter R=0.2 using charged tracks from the ALICE tracking system. The contribution of the azimuthal anisotropy of the underlying event is taken into account event-by-event. The remaining (statistical) region-to-region fluctuations are removed on an ensemble basis by unfolding the jet spectra for different event plane orientations independently. Significant non-zero v2ch jet is observed in semi-central collisions (30-50% centrality) for 20<pTch jet<90 GeV/c. The azimuthal dependence of the charged jet production is similar to the dependence observed for jets comprising both charged and neutral fragments, and compatible with measurements of the v2 of single charged particles at high pT. Good agreement between the data and predictions from JEWEL, an event generator simulating parton shower evolution in the presence of a dense QCD medium, is found in semi-central collisions.
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, J. Klein, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 955 weitere]
Available online 18 December 2015
Gesehen am 29.07.2020